2008
DOI: 10.1055/s-2008-1077509
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance cholangiopancreatography in the diagnosis of primary sclerosing cholangitis

Abstract: MRCP can diagnose PSC but has difficulties in early PSC and in cirrhosis, and in the differentiation of cholangiocarcinoma, Caroli's disease, and secondary sclerosing cholangitis. A positive MRCP would negate some diagnostic ERCP studies but a negative MRCP would not obviate the need for ERCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 21 publications
(25 reference statements)
0
28
0
6
Order By: Relevance
“…31 For the diagnosis of PSC, the conventional radiographic criteria of beading, duct ectasia, and stricturing of the intra-or extrahepatic bile ducts were used. 40,41 All patients diagnosed with PSC were required to have had an endoscopic retrograde cholangiopancreatography or magnetic resonance cholangiopancreatography performed at our center. Hepatic histology or abnormal biochemical tests alone without typical imaging were not sufficient for a diagnosis of PSC.…”
Section: Patientsmentioning
confidence: 99%
“…31 For the diagnosis of PSC, the conventional radiographic criteria of beading, duct ectasia, and stricturing of the intra-or extrahepatic bile ducts were used. 40,41 All patients diagnosed with PSC were required to have had an endoscopic retrograde cholangiopancreatography or magnetic resonance cholangiopancreatography performed at our center. Hepatic histology or abnormal biochemical tests alone without typical imaging were not sufficient for a diagnosis of PSC.…”
Section: Patientsmentioning
confidence: 99%
“…One study has suggested that a numerical score calculated based on three-dimensional MRC may predict progression of bile duct changes but the study lacked ERCP reference (17). A diagnostic MRC, because of its very high specificity for the diagnosis of PSC when diagnostic clinical and biochemical clues are present, obviates a confirmatory ERCP unless therapeutic procedures or ductal sampling are indicated (13,18 Whether or not to perform ERCP in patients with normal high-quality MRC depends on the level of clinical suspicion for PSC and impact of the diagnosis on patients management and prognosis. ERCP is regarded unnecessary in patients with a low level of clinical suspicion, but it could be considered in patients with intermediate or high level of clinical suspicion as suggested by a meta-analysis of MRC diagnostic performance (13).…”
Section: Esge/easl Recommend That As the Primary Diagnostic Modalitymentioning
confidence: 99%
“…[71,72] MRI features of PSC have been mainly described using two dimensional (2D) MRC, and have shown no correlation with disease severity measured by MRS. [73,74] Using the newer three-dimensional (3D) MRC, visibility of the biliary tree has improved. [75] Systematic analysis of bile ducts and liver parenchyma over time visualized by 3D MRC has recently been used to discriminate two radiologic PSC disease patterns; stability and worsening.…”
Section: Magnetic Resonance Cholangiopancreatography (Mrc)mentioning
confidence: 99%